Pengaruh Brand Awareness Dan Brand Trust Terhadap Minat Beli Smartphone Iphone Pada Mahasiswa Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Riau - Juni Juni; Mashur Fadli (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine and explain the influence of Brand Awareness (X1), Brand Trust (X2) on Purchase Interest (Y) of iPhone Smartphones among students of the Faculty of Social and Political Sciences, University of Riau. The data for this study were obtained based on questionnaires distributed to students of the Faculty of Social and Political Sciences, University of Riau who were interested in purchasing iPhone smartphones. The sampling as the object of the study was 98 respondents. This research method is a quantitative method. The data analysis technique used is multiple linear regression analysis. Based on the results of the data analysis that has been carried out, it was found that brand awareness (X1) has a positive and significant effect on purchase interest (Y), brand trust (X2) has a positive and significant effect on purchase interest (Y) and brand awareness (X1) and brand trust (X2) have a positive and significant effect on purchase interest (Y) iPhone smartphones among students of the Faculty of Social and Political Sciences, University of Riau.